Characteristic feature of oxygen cost at simulated laboratory triathlon test in trained triathletes - Miura, H.; Kitagawa, K.; Ishiko, T. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: The present study was carried out in order to investigate the respiratory and circulatory features during a simulated laboratory triathlon test in trained triathletes. METHODS: Experimental design: Sixteen male triathletes were divided into superior (n = 8) and slower triathletes (n = 8) according to their race time. These subjects performed both maximal exercise tests and a simulated laboratory triathlon test (ST). The latter test consisted of flume-pool swimming for 30 min, ergometer cycling for 75 min and treadmill running for 45 min as a continuous task. The exercise intensity was 60% of VO2 max during swimming, cycling and running, respectively. RESULTS: In slower triathletes, VO2, minute ventilation (VE), heart rate (HR) and temperature of external auditory canal were increased from an earlier stage compared with those in superior athletes. The percent increase (delta) of VO2, VE and HR between the 10th and last min of cycling and running stages in superior triathletes were significantly smaller than those in slower athletes. The oxygen cost (oxygen uptake/running velocity) of running stage was significantly lower in superior triathletes (0.220 +/- 0.020 ml.kg-1.m-1) compared with slower athletes (0.264 +/- 0.014 ml.kg-1.m-1). CONCLUSIONS: These results suggest that superior triathletes performed ST more economically than slower athletes and had excellent thermoregulatory adaptation.